DILEMA HUKUMAN FISIK DALAM PENDIDIKAN: Telaah Kritis Perspektif Empat Aliran Pembelajaran - Thulfitrah B., Nurlathifah; Putra B., Muhammad Nuralamsyah; N., Abd. Muid; Lubis, Zakaria Husin (Jurnal Diskursus Islam, 2025)
This article discusses the practice of corporal punishment in education has been the subject of much debate among academics and educational practitioners. Some argue that corporal punishment is effective in instilling discipline, while others highlight its negative impact on students’ psychological and emotional development. This study aims to analyze the use of corporal punishment in education from the perspective of four major learning theories: behaviorism, cognitivism, humanism and constructivism. The research method used is a literature study by reviewing various literatures that discuss the relationship between learning theories and the effectiveness of corporal punishment. The results showed that behaviorism tends to justify the use of corporal punishment as a negative reinforcement tool to reduce undesirable behavior. In contrast, cognitivism, humanism and constructivism reject corporal punishment because it can hinder the learning process, undermine intrinsic motivation, and disrupt students’ social and emotional development. The implications of these findings emphasize the importance of implementing alternative discipline methods that are more humanistic and understanding-based, such as positive reinforcement and reflective approaches. Thus, this study contributes to educators in designing discipline strategies that are more in line with modern educational principles that emphasize effective and empathic learning.